The ABC's of chemistry; an illustrated dictionary - Gallant, Roy A. (Doubleday, 1963)
This dictionary contains an alphabetical listing of more than 500 basic chemical terms and concepts. The second section consists of many additional tables including those dealing with acids, foods, plastics and synthetic fibers.